Crystal structure of-(1S,4aR,5S)-5,6,7-trihydroxy-8-isopropyl-1-methyl-1,2,3,4,5,10,11,11a-octahydro-4a,1-(epoxymethano)dibenzo[a,d][7]annulen-13-one C20H26O5 - Yu Jiao; Zhao Chen-Liang; Luo Yu-Ling; Yang Ya-Xin; Zhang Jing-Jie (Zeitschrift für Kristallographie - New Crystal Structures)
C20H26O5, monoclinic, P21, a = 14.0782(12) Å, b = 8.6399(7) Å, c = 14.6891(13) Å, β = 101.9593(9), V = 1747.93(3) Å3, Z = 4, R gt(F) = 0.0275, wR ref(F 2) = 0.0736, T = 100(1) K.